Review of the book Geography and Phenomenology: the misplacement of Martin Heidegger’s humanist assimilation - Cozer Chiabai Silva, Akylla (Geografares, 2024)
Review of the book by Luis Carlos Tosta dos Reis and Josimar Monteiro Santos. Geography and Phenomenology: the misplacement of Martin Heidegger’s humanist assimilation. Curitiba: Editora Appris, 2024.